2019
DOI: 10.7759/cureus.6480
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Pneumothorax with Subsequent Subcutaneous Emphysema

Abstract: This presentation reports a case of a 67-year-old former smoker who presented to the emergency department with new-onset hemoptysis. During the workup, a left lung mass was identified. During the biopsy, he experienced a pneumothorax. The procedure had to be aborted, and a small-sized chest tube was placed. The following day, the patient underwent a successful second lung biopsy, but a day later he developed significant subcutaneous emphysema despite having a chest tube. The same day, the smaller chest tube wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Very few number of case reports of severe SE have been reported in the literature. 4,5 Free air in the subcutaneous thoracic region can be caused due to parietal pleural injury that further diffuses in myofascial planes dissecting them to cause severe subcutaneous emphysema, as discussed in our case. There is a significant correlation between the underlying lung parenchymal condition, which in our case study showed emphysematous changes and the increase in the risk of pneumothorax, and further in subcutaneous emphysema.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Very few number of case reports of severe SE have been reported in the literature. 4,5 Free air in the subcutaneous thoracic region can be caused due to parietal pleural injury that further diffuses in myofascial planes dissecting them to cause severe subcutaneous emphysema, as discussed in our case. There is a significant correlation between the underlying lung parenchymal condition, which in our case study showed emphysematous changes and the increase in the risk of pneumothorax, and further in subcutaneous emphysema.…”
Section: Discussionmentioning
confidence: 70%
“…2 Patient position, small size of the lesion, multiple pleural punctures, and distance of the lesion from the pleura increases the risk of pneumothorax proportionally. 1 3 4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this method is thought to provide a rapid and cosmetically appealing outcome compared with more invasive alternatives such as cervical mediastinotomy [ 5 ]. Our management largely focused on the right pneumothorax evacuation [ 12 ]. The patient’s SE continued to improve throughout her hospital stay, and she did not require blow holes or infraclavicular incisions.…”
Section: Discussionmentioning
confidence: 99%